(untitled) (Altre Modernità, 2013)
In 1906 the Argentinian author Leopoldo Lugones published Las fuerzas extranas. In this collection of short stories Lugones places his interests in spiritism and science at the service of fiction and modernist prose. Lugones furthermore embraces aesthetically the theosophic doctrine envisaging a quest for absolute perfection through a process of renewal and reincarnation of the individual; it is within this framework that a number of apocalyptic episodes found in Las fuerzas extrañas are to be interpreted, pointing as they do in an intertextual game to specific Biblical passages which illustrate the theosophic stand of the author.